Niveles de glucemia y hemoglobina en pacientes diabéticos que reciben educación y los que no reciben, en la ciudad de Loja - Becerra Guamán, Diana Maribel (2014)
Diabetes is a chronic illness that requires continuing medical care and self-management by the patient to prevent acute complications and reduce them long term through education incorporated into their daily lives. It is defined as an alteration in the metabolism of carbohydrates, proteins and lipids, which is the result from the imbalance between the available insulin and insulin needed. Through this research seeks to determine and analyze blood glucose and glycosylated hemoglobin in diabetic patients who are educated and those who are not, in Loja city. With this determines the importance of incorporating diabetes education to patients who have it. By using the scientific method and by collecting data through a personal file for each patient; which includes glucose and glycosylated hemoglobin laboratory examinations of the Brigade Hospital № 7 Loja Data of glucose values by glucometer strips (two controls per week during the month of february and may). After tabulating and analyzing was determined that the levels of glucose and glycosylated hemoglobin are better values in diabetic patients who come regularly and irregularly to control and receive education, in comparison to those with did not receive any education. Demonstrating with it, that education is a very influential indicator and self-control of diabetes. Words claves: diabetes mellitus, glucose, glycosylated hemoglobin, education.